Hepatitis B virus mother-to-child transmission in Namibia: transmission dynamics and possibilities for elimination - Tamandjou Tchuem, Cynthia Raissa (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.